A comparison of match external load demands across women`s collegiate field sports - Kuhlman, N. M.; Jagim, A. R.; Jones, M. T.; Feit, M. K.; Fields, J. B. (The Journal of Strength and Conditioning Research, 2025)
Historically, soccer (SOC), lacrosse (LAX), and field hockey (FH) have been grouped together as "field sports" due to their intermittent nature of match play and similar physiological demands. However, questions have emerged regarding potential variations in demands between sports. The purpose of this study was to compare external match workloads between collegiate women's SOC, LAX, and FH, and examine within-sport positional differences. Athletes (SOC: n = 15; LAX: n = 15; FH: n = 14) wore a global positioning system device during all matches throughout a competitive season. External load metrics included in the analysis were total distance (TD), sprint distance (SD), accelerations (>3 m·s-2), sprint efforts (SE), player load (PL), PL per minute (PL/min), top speed (m·s-1), and distances covered in select speed zones. Soccer performed higher external load volumes (TD, PL) (p = 0.025) but incurred lower intensities (SD, SE, accelerations) (p < 0.001) compared with LAX and FH. Within-sport positional differences were apparent in SOC (p < 0.001-0.018), LAX (p < 0.001-0.045), and FH (p < 0.001-0.004). However, FH exhibited more positional variance in external load metrics compared with SOC or LAX. Field hockey midfielders covered greater volumes (TD, PL) compared with attackers and defenders (p < 0.001), while attackers sustained greater intensities (SD, SE, top speed) compared with midfielders and defenders (p < 0.004). Results indicate that there are significant differences in external workload parameters between sports and across positions. Practitioners should tailor sport-specific and position-specific programs to match demands, and future research should explore the proposed categorizations of LAX as a "fast collision invasion sport," FH as a "fast contact invasion sport," and SOC as a "slow contact invasion sport."